Diagnostic Challenges in Retinoblastoma with Panophthalmitis-Like Manifestation: A Case Report - Nugrahaputra, Rino; Barliana, Julie Dewi (Majalah Oftalmologi Indonesia, 2025)
Purpose: To highlight the importance and challenges of diagnostic examination and modalities to diagnose retinoblastoma with varieties of manifestation such as panophthalmitis-like. Case Report: A 4-year-old boy presented with red and swollen right eye since two days prior to admission. The position of the right eye was hypotrophy with restricted eye movement towards all directions and there was a presence of proptosis with edema, spasm, hyperemia with yellowish crust. Ultrasonography result came with severe anterior-posterior vitreous haziness with calcified mass suggesting an intraocular tumor of the right eye. Orbital CT-scan was performed and suggestive of panophthalmitis with superior palpebra abscess of the right eye. The inflammation was proposed due to prior intraocular surgery of cataract extraction and trabeculectomy that led to progression and worsening of the retinoblastoma, such invasive surgery led to atypical presentation of panopthalmitis-like. Patient initial visit was due to symptoms of leukocoria and squinting, but even though ocular ultrasonography was performed, the patient had failed to be diagnosed with retinoblastoma. Patient had CT scan and was confirmed of an intraocular mass with calcification inside the right eye with some palpebral abscess. MRI was performed to confirm the extension of the mass, which fortunately did not extend outside the eye. The patient then underwent chemo reduction therapy, before finally got enucleation with dermatofat graft surgery. Histologic examination confirmed the diagnosis of retinoblastoma. This case was an example of how sometimes clinical misdiagnosis among retinoblastoma can happen which can be due to inadequate diagnostic examination or atypical presentation. Preventing clinical misdiagnosis of retinoblastoma can improve the treatment and likelihood of survival of patients with retinoblastoma. Conclusion: Clinical misdiagnosis of retinoblastoma can happen without adequate diagnostic tools and prowess which may result in mismanagement and/or delayed treatment leading to poorer prognosis of patient with retinoblastoma.